Rotavirus and Severe Childhood Diarrhea - Umesh D. Parashar; Christopher J. Gibson; Joseph S. Bresee; Roger I. Glass (Emerging Infectious Diseases, 2006)
Studies published between 1986 and 1999 indicated that rotavirus causes ≈22% (range 17%–28%) of childhood diarrhea hospitalizations. From 2000 to 2004, this proportion increased to 39% (range 29%–45%). Application of this proportion to the recent World Health Organization estimates of diarrhea-related childhood deaths gave an estimated 611,000 (range 454,000–705,000) rotavirus-related deaths.